Sensitivity analysis using simulations for a ground source heat pump – implementation on a solar passive house - Ilisei Gheorghe; Catalina Tiberiu; Gavriliuc Robert (E3S Web of Conferences, 2019)
Having in sight the need for a strong reduction in CO2 emissions and the fluctuation of the price of fossil fuels, the ground source resources alongside with the ground source heat pumps are becoming more and more widespread for meeting the heating/cooling demand of several types of buildings. This article targets to develop the thermal modelling of borehole heat storage systems. Trying to emphasize some certain advantages of a GSHP (ground source heat pump) with vertical boreholes, a case study analysing a residential solar passive house is presented. The numerical results are produced using different modelling software like DesignBuilder, EED (Earth Energy Designer) and a sizing method for the length of the boreholes (ASHRAE method). The idea of sizing the length of boreholes (main design parameter and good index in estimating the system’s cost) using two different methods shows the reliability of this modelling tool. The study shows that borehole’s length of a GSHP system can trigger a difference in electricity consumption up to 22%. Moreover, this sensitivity analysis aims to prove that the design of the whole system can be done beforehand just using modeling tools, without performing tests in-situ.